Implementasi Program Puspaga Dalam Memperbaiki Pola Asuh Orang Tua Kepada Anak Di Kelurahan Embong Kaliasin - Navella Marchelina; Anggaraeny Puspitaningtyas (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research was conducted with the aim of finding out the form of implementation of the PUSPAGA (Family Learning Center) program as an effort to improve parents' parenting patterns. in children in Embong Kaliasin Village. The existence of this research is due to the background related to the problem of parenting patterns in children which tend to still have many errors in the Embong Kaliasin sub-district community. The implementation theory applied in this research is the theory put forward by George C. Edward III with four variables, namely communication, resources, disposition and bureaucratic structure. The research method applied is a qualitative research method with a case study approach. This research applies data collection techniques through observation, documentation and notes. The data analysis techniques applied in this research are data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the PUSPAGA program has referred to the theory by George C. Edward III which has four variables, namely communication, resources, disposition and bureaucratic structure.